Biokinetic model-based multi-objective optimization of Dunaliella tertiolecta cultivation using elitist non-dominated sorting genetic algorithm with inheritance. (October 2017) - Sinha, Snehal K.; Kumar, Mithilesh; Guria, Chandan; Kumar, Anup; Banerjee, Chiranjib
Graphical abstract: Highlights: Multi-objective optimization of Dunaliella tertiolecta cultivation using NPK fertilizer. Maximizing algae-biomass and lipid production with minimum cultivation time and cost. Finding the best strategy for optimal algal cultivation. Optimal control strategy for large scale algae-biomass production. Application of NSGA-II with adapted jumping gene with altruism and inheritance. Abstract: Algal model based multi-objective optimization using elitist non-dominated sorting genetic algorithm with inheritance was carried out for batch cultivation of Dunaliella tertiolecta using NPK-fertilizer. Optimization problems involving two- and three-objective functions were solved simultaneously. The objective functions are: maximization of algae-biomass and lipid productivity with minimization of cultivation time and cost. Time variant light intensity and temperature including NPK-fertilizer, NaCl and NaHCO3 loadings are the important decision variables. Algal model involving Monod/Andrews adsorption kinetics and Droop model with internal nutrient cell quota was used for optimization studies. Sets of non-dominated (equally good) Pareto optimal solutions were obtained for the problems studied. It was observed that time variant optimal light intensity and temperature trajectories, including optimum NPK fertilizer, NaCl and NaHCO3 concentration has significant influence to improve biomass and lipid productivity under minimum cultivation time and cost. Proposed optimization studies may be helpful to implement the control strategy in scale-up operation.